When a government attempts to institutionalize and regulate deliberative democracy: the how and why from a process-tracing perspective. Issue 1 (2nd January 2017) - Ravazzi, Stefania
ABSTRACT: Over the last few decades, public deliberation has spread in many countries, but this has occurred mostly through experiments and pilot projects. Recently, some countries have taken some steps forward by introducing participatory policies in order to institutionalize citizen involvement practices in the policy-making processes. Among these countries, France and Italy, and Tuscany in particular, have been recognized as clear examples of democratic governments that have initiated public programs to systematically apply deliberative processes to policy-making. These programs seem particularly challenging as far as the legitimacy of the democratic representative institutions and the role of politicians are concerned. Therefore, whatever leads a government to initiate such a policy deserves attention, and a theory on the particular model that can characterize the initiation of these policies is needed. The paper has the aim of proposing a hypothesis on the causal mechanism that can lead to the initiation of such a policy. A within-case study of the Tuscan case, which at present is recognized as the most advanced laboratory of deliberative democracy, is presented. The application of process tracing allows an analytical explanation to be made, which could be used as a theoretical base for further research on the topic.